Digital-marketing as an innovation control element (Economics and region, 2021)
The article presents the results of the study of the essence and approaches of the interpretation of the concept of "digital marketing", reveals the main tools and methods of this phenomenon. The effectiveness of the impact of the introduction of digital marketing on modern business is determined. The concepts, possibilities and advantages of digital marketing are defined, the analysis of a condition of the market of digital marketing in Ukraine and modern tendencies of digital marketing is carried out. Modern management tools are highlighted and the issues of supporting marketing decisions at different levels of management with the help of information and communication technologies and systems are considered. The main advantages of digital marketing are indicated and the main differences from traditional means of communication are considered. The main problems on the way to the effective use of digital marketing in order to reach the target audience and increase sales are identified.
Keywords: digital marketing; social networks; advertising; internet marketing; digital technologies; management tool